2014
DOI: 10.1080/19475705.2014.983187
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of present-day inter-seismic deformation in Kopili fault zone of north-east India using GPS measurements

Abstract: Current study reports the present-day inter-seismic deformation of Kopili fault zone of north-east India and slip rate estimate of Kopili fault using five epochs of global positioning system (GPS) data collected from seven campaigns and five permanent sites. The rate of baseline length change of the GPS sites across the Kopili fault indicates »2.0 mm/yr EÀW convergence across the fault. The fault parallel GPS site velocities clearly indicate dextral slip of the Kopili fault. The fault normal velocities show co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…6), would actually result in an M W of 8.4. Evidence for past megathrust ruptures in the Bhutan Himalaya have been provided by other recent studies (e.g., Berthet et al, 2014;Le Roux-Mallouf et al, 2016;Hetényi et al, 2016a) and similar structural segmentation is suggested from gravity anomalies (Hetényi et al, 2016b).…”
Section: Crustal Structure and Mht In Bhutansupporting
confidence: 64%
See 1 more Smart Citation
“…6), would actually result in an M W of 8.4. Evidence for past megathrust ruptures in the Bhutan Himalaya have been provided by other recent studies (e.g., Berthet et al, 2014;Le Roux-Mallouf et al, 2016;Hetényi et al, 2016a) and similar structural segmentation is suggested from gravity anomalies (Hetényi et al, 2016b).…”
Section: Crustal Structure and Mht In Bhutansupporting
confidence: 64%
“…Recent paleoseismic studies along the Main Frontal Thrust (MFT) in Bhutan suggest the occurrence of one or more large earthquakes in the last millennium (Berthet et al, 2014;Le Roux-Mallouf et al, 2016). Re-interpretation of historical damage reports provides additional evidences for an M8 earthquake in Bhutan in 1714 AD ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As per Kundu & Gahalaut (2013), the Kopili fault located to the east of the Shillong Plateau, was also undergoing active deformation with a slip of 2.9 ± 1.5 mm/year. Barman et. al.…”
Section: Seismotectonics Of Kopili Regionmentioning
confidence: 99%
“…The slip rate for the present study is considered to be 1.3 mm/year as per the Northeast India permanent network baselines (Jade et al 2007). The slip rate associated to the Kopili Fault is contributing to accumulation of seismic moment to the order of »70.74 £ 10 15 N m/year (Barman et al 2016). The input parameters (Tables 1 and 2) for the fault characteristic are estimated from existing literatures (Hanks & Boore 1984;Wells & Coppersmith 1994;Jade et al 2007;Angelier & Baruah 2009;Bhattacharya et al 2010;Kayal et al 2006Kayal et al , 2012.…”
Section: Study Area and Databasementioning
confidence: 99%
“…Strain map along with geodetic velocities around the Kopili Fault (modified afterKreemer et al (2003) andBarman et al (2016).…”
mentioning
confidence: 99%